Climate change induced salinity intrusion and its implications for agriculture - Pathak, Himanshu; Pal, Barun Deb; Joshi, Pramod K. (2018)
An estimated 1.06 million hectare of arable land in Bangladesh and 6.7 million hectares in India is affected by salinity (Rabbani 2013). Salinity intrusion adversely affects the livelihoods of farmers, especially rice cultivators and fisherfolks, vegetations, soil quality, and infrastructure in these areas (Habiba et al. 2014). The net cropped area in coastal Bangladesh has been decreasing over the last few years due to several factors and many studies have identified salinity as the chief cause for yield reduction in coastal agriculture (Baten 2015). Groundwater contamination due to saline water and similar adverse impacts on agriculture and livelihoods are also increasing in coastal India, especially in Kerala, Karnataka, Odisha, and Andhra Pradesh (Naidu et al. 2013). The extent and intensity of salinity in the coming years are likely to increase due to climate change induced saltwater intrusion.